Sistem Informasi Pengelohan Data Pasien Rawat Inap Berbasis SMS Gateway - Haryanto Haryanto; Bambang Priyatmoko (STIE AUB Surakarta, 2015)
Puskesmas Gesi is a public health service centre institution under Sragen Regency Government having responsibility in public health sector. Medical data service and process still run less effectively because all of activities are carried out manually either recording in the form of document or archive. Therefore that was less effective and error often occurs. This research and system design employed library study with pieces analysis method and UML design. Library study was a process of looking for theoretical basic sources to be discussed in this topic. The analysis method used was to analyze the performance of Puskesmas by conducting survey and identifying the information need. UML design represented the system plot to be made with use case, class diagram, activity diagram, interface designing, database designing using SQL Server 2000, report writing using crystal report 8.5, and supporting software using Microsoft Visual Basic 6.0. This design and development of Inpatient Data Processing Information system facilitated the medical personnel in processing and recording medical personnel data, patient data, drug data, outpatient data, inpatient data, and report.Keywords: Pieces Method, UML, SQL, Crystal Report and Visual Basic 6.0